Stochastic comparisons of linear degradation and failure time models with dependent failure modes - Ling, Xiaoliang; Zhang, Jiaojiao; Wei, Yinzhao (Communications in statistics. Theory and methods, 2024)
The paper considers a reliability model for system which fails due to degradation failure or catastrophic failure. The linear degradation path is adopted to model the degradation process, and catastrophic failure rate is dependent on the degradation rate. Firstly, we conduct some stochastic comparisons between two systems when their respective degradation rate variables are ordered in the sense of various stochastic orders. Secondly, we conduct some stochastic comparisons between two systems with different conditional catastrophic failure rates. Finally, we give some examples with respect to some well-know models to illustrate the validity of the results.